2018
DOI: 10.1039/c8em00057c
|View full text |Cite
|
Sign up to set email alerts
|

As and Sb are more labile and toxic to water spinach (Ipomoea aquatica) in recently contaminated soils than historically co-contaminated soils

Abstract: Elevated concentrations of As and Sb impact environmental quality and human health. In this study total and bioavailable As and Sb were measured from recently and historically contaminated soils and the phytotoxicity of these soils was evaluated with Ipomoea aquatica (35-d exposure from germination) using biomass, length of plant tissues and photosynthetic efficiency. As and Sb were both present within the soil (co-contaminated). The bioavailable As and Sb in soils were determined by a Sequential Extraction Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The physical and chemical properties—soil pH, particle size, soil moisture (percentage), total organic matter (TOM; percentage), total Kjeldhal nitrogen (TKN; milligrams per kilogram), and sodium bicarbonate (Olsen) extractable phosphorus (milligrams per kilogram) were measured before starting the bioasays using the methods outlined in Egodawatta et al (2018; Supplemental Data, Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical and chemical properties—soil pH, particle size, soil moisture (percentage), total organic matter (TOM; percentage), total Kjeldhal nitrogen (TKN; milligrams per kilogram), and sodium bicarbonate (Olsen) extractable phosphorus (milligrams per kilogram) were measured before starting the bioasays using the methods outlined in Egodawatta et al (2018; Supplemental Data, Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Arsenic (As) and antimony (Sb) often co‐occur and are commonly found in plants grown in contaminated agricultural soil near Sb‐mining sites (Casado et al 2007; Mestrot et al 2016; Egodawatta et al 2018). Furthermore, some agricultural fields have become contaminated by the improper disposal of industrial wastes, the application of pesticides and fertilizers, wastewater irrigation, spillage of petrochemicals, and atmospheric deposition (Dahal et al 2008; Wuana and Okieimen 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The difference observed between length of plants in cultivated group was not signi cant. The study of Egodawatta et al (2018) has shown a poor relationship between both length and biomass (in root and shoot) of water spinach and exposure to As concentration under 100 mg/kg in natural contaminated soils. Codling (2014) has also reported an insigni cant reduction in lettuce yield when lettuce is cultivated in naturally As-contaminated soil (133-153 mg As/kg).…”
Section: Biofertilizer Formation and Plant Analysismentioning
confidence: 99%
“…Also, after the addition of metal to a soil, its availability decreases with time, usually because of micropore diffusion, cavity entrapment, occlusion in solid phases by co-presipitation and co-flocculation, surface precipitation or crystal growth (Ma et al, 2006a). Egodawatta et al (2018) claimed that bioavailability of As and Sb depends on soil properties, total soil metalloid concentrations and incubation time, and that percentage of As and Sb bioavailability in historically contaminated soils (~34 years) was <10%…”
Section: Agingmentioning
confidence: 99%
“…Zn was mostly present in an exchangeable fraction but it decreased over time, with 45% of Zn being remobilized into stronger binding sites after 63 days of aging. As a result, in experiments in which metals have been recently added to soils, the availability of metal is greater than in those in which the metals have aged for some period (Sauve, 2002, McBride and Cai, 2016, Egodawatta et al, 2018.…”
Section: Agingmentioning
confidence: 99%